Pengaruh Model Pembelajaran Inkuiri terhadap Hasil Belajar Matematika pada Peserta Didik Kelas VIII SMP Negeri 1 Sumarorong - Nurhidayah Nurhidayah; Irfawandi Samad; Resky Hartono (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2019)
This research is experimental research. The population in this study was all students of Class VIII SMP Negeri 1 Sumarorong. Samples of 42 people consisting of class VIII A of 24 people and class VIII B as many as 18 people taken in random sampling. In this study used test instrument study results, learning model implementation sheet, and student activity sheet. The Data obtained is analyzed using descriptive statistical analysis and inferential statistical analysis. Based on data analysis results, both groups are normal and homogeneous distributions, so that hypothesis testing is performed using Test-t statistics. Based on the test-T statistics obtained: 1) The median value of the experimental class pretests 54.94 while the control class is 53.80, and the average Postest experimental class is 78.17, while the control class is 68. 2) for the implementation of the Inkuiri model's execution sheet after analyzed was obtained an average of 94%, as well as the activity sheet of students for the experimental class obtained 61% while the control class was 38%. and test-T acquired significant 0.024 < 0.05 This indicates that H0 was rejected and H1 received. Thus, it can be concluded that the Learning model inquiry affect the outcome of mathematics for students of class VIII SMP Negeri 1 sumarorong.